STUDY OF THE RELATIONSHIP BETWEEN KRAS GENE MUTATIONS AND GENDER, AGE AND RACE IN COLORECTAL CANCER PATIENTS RESIDING IN THE REPUBLIC OF KAZAKHSTAN - D. R. Kaydarova; K. K. Smagulova; N. A. Chichua; E. A. Ukolova; A. Z. Kurmankulova; E. I. Ishkinin (Сибирский онкологический журнал, 2020)
In 2016 3158 patients with colorectal cancer (CRC) were registered in the Republic of Kazakhstan, out of them, 1,484 patients died. Colorectal and colon cancers are the 8th and the 5th leading causes of mortality, respectively. One of the most significant events in the molecular pathogenesis of CRC is an activating mutation in the KRAS oncogene. Recently, studies of the KRAS gene mutation and analysis of its relation with the clinical course of CRC have been carried out in different countries. The effect of gender and age on the KRAS gene status in CRC remains a subject for discussion. The purpose of this study was to study the relationship between the KRAS gene status and gender, age and race in colorectal cancer patients residing in the Republic of Kazakhstan. Material and methods. Data on 332 patients with CRC for the period from 2010 to 2014 were studied. KRAS test was performed using BioLink kits to detect mutations in 12 and 13 codons of 2 exon using allele-specific PCR method. Results. In our study, the frequency of KRAS gene mutations in CRC patients residing in the Republic of Kazakhstan was 44.9 %. The frequency of mutations in the studied codons among women and men was the same. When analyzing the mutation frequency of the KRAS gene, it was revealed that among both sexes the G12D mutation was more often observed. The least common mutations were G12C, G12S, which occurred in both sexes (up to 5 % of cases). The analysis of the dependence of the mutation on the race of the patients revealed some predominance of the wild type in the Asian group – 94 (51.4 %), while Europeans were more often detected with the KRAS mutation – in 81 (54.4 %) patients. Mutation of the KRAS gene was more frequently observed in the group of older patients.